Bahasa dan Konstruksi Solidaritas Antaretnis Masyarakat Transmigran di Nusa Tenggara Barat - Kamaludin Yusra; Yuni Budi Lestari (Antropologi Indonesia, 2011)
This study is aimed at identifying linguistic features, indexing ethnic identities, and inter-ethnic solidarity in transmigration contexts. Data were collected through interview, documentation and ethnography of various transmigrate communities on Sumbawa island. The data were then analyzed qualitatively with the ethnography of speaking and interaction analysis. The study found that (a) Ethnic identities in the migrant areas can be linguistically identified in four forms: orang aida (to refer to Sumbawa people), orang kalembo ade (for Bima people), dengan batur (for Sasak people) and orang beli (Balinese people). (b) These people were identifiable in the way they articulate particular sounds: orang beli (the Balinese) were identified in terms of dominant use of alveolar retroflexed, orang batur (the Sasak) were identified in the way they marked use of alveolar retroflexed, and orang kalembo ade (the Bima people) were identified through their articulation of closed central vowel as open low front vowel. It was also found that the forms had been used to construct ethnicity and interethnic solidarity between participants. The use of ana and ente in interaction indicated solidarity regardless of differences in age and social status. Key words: language and society, contextualization, ethnicity, solidarity, inter-cultural communication, transmigration